Association Between Deliberate Self-Harm and Coping in Adolescents: A Critical review of the Last 10 Years - Guerreiro, Diogo (2013)
Coping is commonly associated with deliberate self-harm (DSH) in adolescents. This article reviews the published literature from 2000 to 2010, aiming to highlight the current evidence supporting this association. Eighteen studies met the inclusion criteria, a total sample of 24,702 subjects was obtained and 17% were DSH cases. Emotion-focused coping style and in particular avoidant coping strategies have consistently been associated withDSH in adolescents. Problem-focused coping style seems to have a negative relation. Most studies were cross-sectional, which seriously limits our conclusions on causality. There is a clear need for more systematic studies, performed in accordance with consensual methodology.